New Constraints on Slip Deficit on the Aleutian Megathrust and Inflation at Mt. Veniaminof, Alaska From Repeat GPS Measurements. Issue 4 (12th February 2021) - Drooff, Connor; Freymueller, Jeffrey T.
Abstract: We employ an enhanced data set of Global Positioning System (GPS) velocities to reassess the slip deficit along the plate interface of the Alaska‐Aleutian subduction zone. An examination of velocities of sites near Mt Veniaminof, located in the southwest Alaska Peninsula, shows that existing models for tectonic deformation do not accurately predict the local velocity field along this section of the peninsula. In a combined model, we solve for the volcanic inflation signal on the edifice of Mt. Veniaminof and reassess the variations in trench coupling outboard of the volcano. The interseismic deformation near Veniaminof and the eastern Shumagin islands requires an additional model segment with higher slip deficit than the western Shumagin islands. This segment appears to have been the main rupture patch of the 2020 M 7.9 Simeonof earthquake. The volcano inflated over the time period of 2005–2017, although at a lower rate than in 2002–2005. Plain Language Summary: Subduction zones globally display marked variations in slip behavior along their length. The subduction zone off the coast of the Alaska Peninsula is one such example, where the shallow section of the plate boundary transitions from being fully locked to fully creeping over the span of roughly 250 km. We show that surface deformation data gathered from the region near Mt. Veniaminof and in the eastern Shumagin islands indicates a particular region of 'sticking' behavior, which appears to have been the focus of rupture in the 2020 M 7.8 Simeonof Earthquake. We find that the data from the eastern Shumagin islands are best explained by these sites lying directly on top of an abrupt along‐strike boundary in the slip behavior of the subduction zone, providing an important observation of how the earthquake cycle manifests itself in regions where plate coupling is not uniform along the length of the subduction zone. Key Points: We find a distinct segment with a different slip deficit distribution that lies on the section of Alaska‐Aleutian subduction zone outboard of Mt. Veniaminof and the eastern Shumagin islands The 2020 M 7.8 Simeonof Earthquake appears to have ruptured this section of the megathrust, with coseismic and postseismic slip extending both westward and downdip along the plate interface Mt. Veniaminof exhibits a steady inflationary signal between 2005 and 2017 that is smaller than it's 2002–2005 inflation